2008
DOI: 10.1253/circj.72.427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Contrast Agent on Long-Term Renal Function and the Efficacy of Prophylactic Hemodiafiltration

Abstract: he incidence of hypertension (HT) and of diabetes mellitus (DM) has been continuously increasing with the aging of society and changes in lifestyle. HT and DM can be factors in cardiac and vascular disorders, and chronic renal insufficiency (CRI), so the probability of encountering coronary artery disease in a patient with CRI is relatively high. Contrast-induced nephropathy (CIN) is defined as acute renal dysfunction manifesting as temporary elevated serum creatinine level (Scr) because of the use of a contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…15 CIN accounts for 12% of the acute kidney injury cases that occur in hospitals, and approximately 30% of patients develop renal dysfunction or chronic renal failure. 16 An animal model using old spontaneously hypertensive male rats showed that high osmolar contrast media could enhance the progression of glomerulosclerosis and renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 CIN accounts for 12% of the acute kidney injury cases that occur in hospitals, and approximately 30% of patients develop renal dysfunction or chronic renal failure. 16 An animal model using old spontaneously hypertensive male rats showed that high osmolar contrast media could enhance the progression of glomerulosclerosis and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely to be considered that the contrast-induced elevated oxidative stress was transient because a rise in sCr level usually returns to the basal level within 2 weeks. 15 It might also be appropriate to consider that the patients with an increased sCr level after coronary angiography, even within a normal sCr level range, have inapparent renal insufficiency. Administration of a contrast agent might work as a challenge test to become evident in renal insufficiency.…”
Section: Prediction Of Chronic Renal Insufficiencymentioning
confidence: 99%
“…Previous studies reported that the use of contrast media is an independent factor that promotes chronic renal insufficiency and even mild renal insufficiency is associated with a dramatic increase in adverse clinical events, both periprocedurally and during long-term follow-up, in patients undergoing percutaneous interventions. 2,20 In particular, renal insufficiency is reported to be associated with increased risk of infection, upper gastrointestinal bleeding and cerebral infarction, which were causes of death in the present study. [21][22][23][24] Thus, we hypothesize that sodium bicarbonate attenuates acute renal injury after exposure to contrast media and improves long-term outcomes by reducing persistent renal insufficiency caused by glomerular over-filtration in residual nephrons and the release of neurohormones that reduce renal blood flow.…”
Section: Persistent Renal Injury and Long-term Clinical Outcomesmentioning
confidence: 48%
“…It has been reported that 60-90 % of the contrast medium is removed during 1 session of hemodialysis. Clinical studies have been conducted on the basis of these findings to investigate the efficacy of hemodialysis, hemodiafiltration, and hemofiltration in the prevention of CIN [160][161][162][163][164][165][166][167][168][169]. However, most studies could not demonstrate the efficacy of these procedures in the prevention of CIN.…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%